Mechanical characteristics of Avlamè lateritic gravel improved with granite crushed for its use in road construction in benin - HOUANOU, KOCOUVI AGAPI; Dossou, Kpomagbé Serge; PRODJINONTO, Vincent (My University, 2022)
Lateritic gravels are the most abundant road materials used in pavement foundations. With the scarcity of good quality materials, the recourse to lateritic gravels having weak technical characteristics, like the lateritic quarry of Avlamè Benin, is felt with the high price of stabilizers like cement, other methods must be explored in cooperation in order to reduce the cost of stabilization and, consequently, the cost of road construction and the risks related to the environmental pollution In this respect, it is imperative to determine the technical characteristics of the lateritic gravel of Avlamè improved with granitic crushed stone 0/31.5 for its use in the base course of flexible pavements. Thus, an experimental study on Avlamè lateritic gravel with different percentages of granitic crushed stone was carried out following the normative recommendations in road construction. This characterization allowed to highlight the technical properties of the lateritic gravel improved with granite crushed at different percentages. The results obtained show that the pass rate at 80 μm sieve goes from 27.77% to 10.51%, the plasticity index from 17.67% to 11.33%, the dry density at OMC from 2.17 t/m 3 to 2.23 t/m and the CBR index at 95% at OMC from 58.00% to 108.67%. These results show that mix 2 (85%GL+15%CG), mix 3 (80%GL+20%CG), mix 4 (75%GL+25%CG), mix 5 (70%GL+30%CG) and mix 6 (65%GL+35%CG) can be used as a base course for flexible pavements in accordance with the normative requirements of the CEBTP revised in 2019 and the Catalogue of AGEROUTE-Senegal. 3
Keywords: Road materials; Base course; 80 μm sieve pass rate; Plasticity index; Dry density at OMC; 95% CBR index; at OMC